Celebrating 20 years of the UK Dermatology Clinical Trials Network. Part 2: education, training and capacity building. (1st June 2022) - Layfield, Carron P.; Williams, Hywel C.
Summary: In Part 1 of this 2‐part review of the 20th anniversary of the UK Dermatology Clinical Trials Network (UK DCTN), we described its role in developing and supporting clinical trial proposals, elaborating on structure, process and clinical trials activity. This review describes the diverse educational and training activities that the UK DCTN supports. Although not primarily set up as an educational organization, an education and training function emerged organically as the network grew. Education and training also embodies the democratization principle that drove the formation of the UK DCTN, allowing participation from a much wider group of individuals than just senior academics. Far from being a sideline, education and training has now become a major component of the UK DCTN that evolves constantly through changing training curricula and trial methodology developments. Formal UK DCTN training opportunities started in 2007 with competitively awarded annual fellowships for dermatology trainees, followed by similar schemes for general practitioners, Staff and Associate Specialist clinicians and dermatology nurses. These were followed in 2013 by larger groups of trainees who work up specific trial proposals with senior mentors. Finally, a virtual journal club emerged during the pandemic in 2020 in order to reach trainees with little access to academic training. Focused activities with dermatological nurses and patients/carers also take place. Such activities require considerable organization and volunteerism from the co‐ordinating centre and former fellows. Education and training has become an essential component for capacity building to develop clinical trials and succession planning for the UK DCTN. Abstract : This review describes the diverse educational and training activities that the UK Dermatology Clinical Trials Network (UK DCTN) supports. Although not primarily set up as an educational organization, an education and training function emerged organically as the network grew. Education and training also embodies the democratization principle that drove the formation of the UK DCTN, allowing participation from a much wider group of individuals than just senior academics.